2014
DOI: 10.1139/cjfas-2013-0633
|View full text |Cite
|
Sign up to set email alerts
|

Predation costs of impaired chemosensory risk assessment on acid-impacted juvenile Atlantic salmon (Salmo salar)

Abstract: Weak levels of acidification (pH < 6.6) inhibit the ability of fishes to assess predation risk via interference with damage-released chemical alarm cues. While survival benefits associated with behavioural responses to alarm cues have been demonstrated under laboratory conditions, it remains largely unknown whether fishes under natural conditions experience similar benefits. Using hatchery-reared juvenile Atlantic salmon (Salmo salar) as a model organism, we conducted a tethering experiment in reaches of neutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Moreover, changes of behavioral responses showing significant alterations in olfactory abilities with mal-adaptive anti-predator strategies and increased anxiety were observed [12,[27][28][29]. In this context, field experiments have shown that juvenile Atlantic salmon (Salamo salar) experiences greater predation rates [30]. Also, invertebrate taxa have recently been found to be susceptible to elevated pCO 2 , which affected valve movement in three North American freshwater mussels [31].…”
Section: Figure 2 Increased Levels Of Pco 2 Do Not Results From Changes Inmentioning
confidence: 99%
“…Moreover, changes of behavioral responses showing significant alterations in olfactory abilities with mal-adaptive anti-predator strategies and increased anxiety were observed [12,[27][28][29]. In this context, field experiments have shown that juvenile Atlantic salmon (Salamo salar) experiences greater predation rates [30]. Also, invertebrate taxa have recently been found to be susceptible to elevated pCO 2 , which affected valve movement in three North American freshwater mussels [31].…”
Section: Figure 2 Increased Levels Of Pco 2 Do Not Results From Changes Inmentioning
confidence: 99%
“…We acknowledge in addition that tethering, as an experimental methodology, can limit natural predator‐avoidance tactics as well as making organisms more conspicuous to predation, which may act to mask treatment‐level effects (reviewed in Lawrence et al, ). Nevertheless, tethering serves as an important tool in estimating relative rates of predation in wild fish in ecologically‐relevant settings (Elvidge & Brown, ; Lawrence et al, ; Rypel et al, ). Further study is needed to address how cortisol influences fine‐scale risk‐taking and antipredator behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Tethering has been used effectively to assess the risk of predation on teleost fish in natural aquatic environments (see Elvidge & Brown, ; Lawrence et al, ; Rypel, Layman, & Arrington, ). As in previous work (Lawrence et al, ; Rypel et al, ), tethers consisted of a single piece of monofilament fishing line (1.5‐m in length; 2.72 kg test monofilament) attached to the lower jaw of the fish.…”
Section: Methodsmentioning
confidence: 99%
“…These streams have served as the setting for several earlier studies on the chemically-mediated antipredator behaviours of juvenile salmon that reliably demonstrate differences attributable to the loss of alarm cue function [15,25,27]. The salmon used were exclusively young-of-year (0 + ), hereafter referred to as "fry.…”
Section: Study Sitesmentioning
confidence: 99%
“…Consequently, waterbodies can be divided into functional categories of acidic or neutral around a boundary of pH 6.6 based on the different behavioural patterns demonstrated by resident fish. Acid-impacted juvenile Atlantic salmon (Salmo salar) have demonstrated both increased predator mortality in acidic streams relative to neutral ones when they were physically 2 International Journal of Ecology constrained in a tethering experiment [27] and responses of greater strength to remaining visual threat cues [15] when they are free-swimming. However, visual cues are often unavailable and may be unreliable in aquatic habitats, so additional compensatory mechanisms are necessary to explain the persistence of prey populations in acidic streams given their apparent greater vulnerability to predation.…”
Section: Introductionmentioning
confidence: 99%